(untitled) (lectio difficilior, 2002)
This article discusses the basic question of whether the „home“ can be considered a distinctive feature for the study of religious competencies of women and men in ancient civilizations. Did women have more freedom to follow religious practices in the home than outside it? Using the example of funeral rites, the article shows that death provided occasions for women to act in public and on behalf of the community. This applies to Ancient Greece, as well as to Egypt and the Near East, as not only literary evidence, but also the iconography of these cultures show. For different reasons, the power of women in the domain of mourning and wailing was, however, controlled and restricted. In biblical sources, full female authority can only be found in the case of one single mantic woman consulting the dead in her house. Usually, however, the home is not a fovourable setting for the religious self-determination of women, since here they are under the immediate supervision of the pater familias.